Organising white matter in a brain without corpus callosum fibres. (February 2015) - Bénézit, Audrey; Hertz-Pannier, Lucie; Dehaene-Lambertz, Ghislaine; Monzalvo, Karla; Germanaud, David; Duclap, Delphine; Guevara, Pamela; Mangin, Jean-François; Poupon, Cyril; Moutard, Marie-Laure; Dubois, Jessica
Abstract: Isolated corpus callosum dysgenesis (CCD) is a congenital malformation which occurs during early development of the brain. In this study, we aimed to identify and describe its consequences beyond the lack of callosal fibres, on the morphology, microstructure and asymmetries of the main white matter bundles with diffusion imaging and fibre tractography. Seven children aged between 9 and 13 years old and seven age- and gender-matched control children were studied. First, we focused on bundles within the mesial region of the cerebral hemispheres: the corpus callosum, Probst bundles and cingulum which were selected using a conventional region-based approach. We demonstrated that the Probst bundles have a wider connectivity than the previously described rostrocaudal direction, and a microstructure rather distinct from the cingulum but relatively close to callosal remnant fibres. A sigmoid bundle was found in two partial ageneses. Second, the corticospinal tract, thalamic radiations and association bundles were extracted automatically via an atlas of adult white matter bundles to overcome bias resulting from a priori knowledge of the bundles' anatomical morphology and trajectory. Despite the lack of callosal fibres and the colpocephaly observed in CCD, all major white matter bundles were identified with a relatively normal morphology, and preserved microstructure (i.e. fractional anisotropy, mean diffusivity) and asymmetries. Consequently the bundles' organisation seems well conserved in brains with CCD. These results await further investigations with functional imaging before apprehending the cognition variability in children with isolated dysgenesis.